المشكلات الإدارية التى تواجه شعب الدراسات العليا فى كليات جامعة بغداد وسبل معالجتها - أحمد، مي فيصل; أحمد، مها فيصل (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2016)
دراسة ميدانية هدفت إلى تحديد المشكلات الإدارية التي تواجه عمل شعب الدراسات العليا في كليات جامعة بغداد وسبل معالجتها، واعتمدت المنهج الوصفي التحليلي. وتم تحديد مجتمع البحث الذي يتكون من (173) معاونا وعاملا في الدراسات العليا، واختيرت عينة البحث بالطريقة العشوائية البسيطة بنسبة (71.676%) من مجتمع البحث، إذ بلغ عدد أفراد العينة (21) معاونا و(103) عاملين في الدراسات العليا. وتم بناء استبانة تضمنت (٧٤) فقرة موزعة بين مجالات الدراسة. وتأكدت الباحثة من صدقها وثباتها. حللت بيانات البحث باستعمال برنامج (SPSS)، وقامت الباحثة بتطبيق الاستبانة من العام الدراسي ٠١٠ ٢—٢٠١١. وتوصلت إلى نتائج تم تحليلها ومناقشتها على وفق مجالات الدراسة المنظمة وهي؛ (إدارة التعليمات، وإدارة شؤون الطلبة، وإدارة الشعب، وإدارة الاتصال، وإدارة الأفراد، وإدارة المستلزمات والخدمات). A Field study aimed to identify the administrative problems that face divisions in graduate education in faculties of Baghdad University and the methods of handling them and it adopted the descriptive analytically approach and it selected the search community which consists of (173) assistant in graduate education, and the selection of search sample was in simple random method of (71,676%) From the research community, the numbers of sample was (21) assistant and (103) from graduate workers and there was questionnaire included (74) items distributed among the fields of study. The researcher ascertained of it`s sincerity and consistency. Research data were analyzed using the (SPSS), program and the researcher applied the items of research from the academic year 2010-2011 ,and she reached to results which were analyzed and discussed according to fields of study: (instructions management, students management, and divisions management, contacting management, people management, management of supplies and services).
Keywords: التعليم العالى -- المشكلات الإدارية -- الدراسات العليا -- الجامعات والكليات -- جامعة بغداد